High temperature fracture toughness of ceramic coatings evaluated using micro-pillar splitting. (15th March 2019) - Best, James P.; Wehrs, Juri; Polyakov, Mikhail; Morstein, Marcus; Michler, Johann
Abstract: Micro-pillar splitting at temperatures up to 500 °C was used to evaluate the toughness for a series of thin physical vapour deposited ceramic-nitride coatings. When compared to ion beam notched geometries, this testing approach reduces the likelihood of ion impregnation within a material volume where fracture may initiate. A toughness increase with elevated temperature was observed for the nanostructured ceramic coatings; the magnitude of which varied between the coatings. A transmission electron microscopy investigation showed deposition-specific periodic nano-layering within the films as a result of the deposition process, which may explain the observed differences in the toughness trends. Graphical abstract: Unlabelled Image